2006
DOI: 10.1080/09638190500525779
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic determinantsof workers' remittances: Hostversus home country's economic conditions

Abstract: This study examines the determinants of worker's remittances. Variance decompositions, impulse response functions and Granger causality tests derived from a vector error correction model are used to test if remittances are affected by the macroeconomic conditions of the host (remittance sending) or home (remittance receiving) country. Data from Brazil, Colombia, the Dominican Republic, El Salvador, Mexico and the US are used. The results indicate that remittances respond more to changes in the macroeconomic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
56
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 20 publications
6
56
2
Order By: Relevance
“…However, remittance flows to Pakistan do not seem to respond to the host country's economic conditions. This is in contrast to the findings of Schiopu and Siegfried, (2006), Vargas-Silva and Huang (2006) and Kemegue et al (2011) who argue that remittances are more responsive to the host country's economic conditions than to the economic conditions of the home country. The results can be explained by considering the extent to which the migrant is integrated into the formal sector of the host economy.…”
Section: Empirical Findingscontrasting
confidence: 56%
“…However, remittance flows to Pakistan do not seem to respond to the host country's economic conditions. This is in contrast to the findings of Schiopu and Siegfried, (2006), Vargas-Silva and Huang (2006) and Kemegue et al (2011) who argue that remittances are more responsive to the host country's economic conditions than to the economic conditions of the home country. The results can be explained by considering the extent to which the migrant is integrated into the formal sector of the host economy.…”
Section: Empirical Findingscontrasting
confidence: 56%
“…This is unlike earlier studies which tend to ignore the potential effects of demographic and/or risk related factors that may be important in capturing altruistic and investment motivations (VARGAS-SILVA and HUANG, 2006; LIN, 2011). Finally, microeconomic 4 theory provides the foundation for exploring the motives for remittances, which are then captured in a model comprising macroeconomic variables.…”
mentioning
confidence: 52%
“…Generally research on remittances in the LAC region is concentrated on a single country or a minority of countries (SAYAN et al, 2010;VARGAS-SILVA and HUANG, 2006;CASTILLO-PONCE et al, 2011). A number of studies have used bilateral data to study remittances (LUETH and RUIZ-ARRANZ, 2008;FRANKEL, 2011;DOCQUIER et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have documented that that remittance respond positively to an increase in the host country GDP (Glytsos 1997, Silva andHuang 2006;Frankel 2009;Ruiz and Vargas-Silva 2010), and in a negative or counter-cyclical manner during economic downturns, financial crises and natural disasters in the migrant-sending country (Clarke and Wallsten 2004;World Bank 2005;Yang and Choi 2007;Yang 2008;Frankel 2009;Mohapatra et al 2009;Ratha 2010). 3 In terms of the relative importance of home and host country factors, several studies have found that the host country economic conditions appears to be more important compared to home country factors (Swamy 1981;Glytsos 1997;Silva and Huang 2006;Barajas et al 2010).…”
Section: Determinants Of Remittancesmentioning
confidence: 99%